'CARE compliance' of case reports published in Dental Traumatology in the past two decades: A bibliometric analysis. Issue 3 (18th February 2022) - Tewari, Nitesh; Goel, Shubhi; Srivastav, Sukeshana; Mathur, Vijay Prakash; Rahul, Morankar; Chaurasia, Bikash; Raghuthaman, Sruthila
Abstract: Background/Aims: The journal Dental Traumatology (DT) is one of the best resources in the field of dental traumatology. It has always encouraged publication of case reports of good quality. The CARE statement (2011) was developed for uniform and transparent reporting of cases in medical sciences. Since case reports are inseparable from the DT literature, the aim of this bibliometric‐analysis was to evaluate the case reports published in the DT in the last two decades (2001–2021) and assess their compliance regarding CARE guidelines for elucidating the trends in DT and the reporting quality of these papers. Methodology: Two authors independently observed the tables of contents in all issues of DT from 2002–2021 and identified case reports. Selected articles were scrutinized to determine their eligibility. Data extraction was performed, case reports were segregated into domains, and their CARE compliance was evaluated by using a self‐designed‐validated method. Differences between the case reports published in two decades (2002–2011 and 2012–2021) were analysed with the Chi‐square test. Results: A total of 1612 articles published between February 2002 and October 2021 were scrutinized to identify 357 case reports with 277 from the period of 2002–2011 and 80 between 2012 and 2021. The highest number of case reports originated from Asia (2002–2011:135, 2012–2021:28). The CARE compliances of the majority of reports in the decade of 2002–2011 were between 75 and 85% (good) while the CARE compliances of the majority of reports from 2012–2021 were between 85 and 95% (very good) or >95% (excellent). These differences were statistically significant ( p  < .005). Conclusions: The number of case reports published in the decade of 2002–2011 were more than three times the number of case reports published in the decade of 2012–2021. The highest number of reports in both decades were from Asia and belonged to the therapeutic and prognostic domains. The CARE compliances of the reports in the decade of 2012–2021 were better than those from 2002–2011.